Frauen in Führungspositionen: Chancen und Risiken durch die COVID-19-Pandemie; Women as leaders: Chances and risks of the COVID-19 pandemic - Vivien-Sophie Gulden; Stephan L. Thomsen (Wirtschaftsdienst, 2021)
Die geringe Repräsentation von Frauen in Führungspositionen hat die EU-Kommission dazu veranlasst, Maßnahmen und Ziele für eine gleichberechtigte Führungsverantwortung zu definieren. Zeitgleich haben die Corona-Maßnahmen zu tiefgreifenden Veränderungen der Arbeitsorganisation geführt. Neben einem Überblick zur Situation von Frauen in Führungspositionen wird ein Augenmerk auf die Wirkungen der Corona-Maßnahmen gelegt, um Chancen und Risiken zu identifizieren. Diese Maßnahmen können durch Verhaltensänderungen mit sowohl positiven als auch negativen Effekten verbunden sein. Langfristig dürften Frauen von den veränderten Bedingungen jedoch profitieren. – – The low representation of women in leadership positions has induced the EU Commission to define measures and targets for gender equality. Almost simultaneously, the measures adopted in the coronavirus pandemic have led to profound changes in the organisation of work. These can slow or inhibit the process. This article provides an overview of the situation of women in leadership positions and the most important reasons for their underrepresentation. Special attention is paid to the effects of the COVID-19 measures in order to identify opportunities and risks. It becomes clear that the same measures entail both positive and negative effects through behavioural changes. Nevertheless, in the long term, women are likely to benefit significantly from the new conditions.
Keywords: J13; J16; J71; 330; Weibliche Führungskräfte; Gleichberechtigung; Coronavirus